Successful coordination of the distributed network, Natural Hazards Engineering Research Infrastructure - Blain, Cheryl Ann; Ramirez, Julio A.; Edge, Billy L.; Holmes, William; LaChance, Marti; Nelson, Robin; Robertson, Ian; Zehner, Dan (Frontiers in Built Environment, 2025)
A Network Coordination Office (NCO) is at the core of the Natural Hazards Engineering Research Infrastructure (NHERI), a national, 12-component, distributed research network, funded by the National Science Foundation (NSF). NHERI is focused on research that both mitigates damage and increases resilience from natural hazards such as hurricanes and other extreme windstorms, storm surge, tsunami waves, and earthquakes. NCO activities engage all facilities within NHERI, uniting the network’s four diverse component types comprised of experimental facilities, a cyberinfrastructure for data and computing resources, a center for the creation of modeling and simulation tools, and a repository of equipment, software and support for rapid reconnaissance. Outcomes from NCO governance activities include two network-wide summits, five international partnerships, a central scheduling tool, and a means for external evaluation. The NCO’s education and community outreach has established an extremely successful pipeline for engineering education from elementary and secondary educators to undergraduates, graduate students, and early career faculty. The NCO conducts centralized communication activities such as newsletter publication, e-mail announcements, podcasts, and social media engagements that unite the natural hazards research community and amplify NHERI’s impact. Led by the NCO, the NHERI Science Plan presents a long-term vision for the natural hazards research community and serves as a roadmap for future high-impact, high-reward, hazards engineering and interdisciplinary research at NHERI facilities. The NCO also promotes technology transfer through education and one-on-one engagement with researchers. Overall, the NCO unifies and strengthens the research network through its variety of initiatives, amplifying the impact of this multifaceted NSF research network and provides a template for the management of large, distributed research networks.